Pengembangan Media Pembelajaran Interaktif Berbasis Powerpoint pada Pembelajaran IPAS Materi Ada Apa Saja di Bumi Kita Kelas V - Alfionita Gea Saputri; Kartono Kartono; Asmayani Salimi (Journal on Education, 2024)
This research aims to produce a Powerpoint-based Interactive Learning Media product for learning science and science material on What's on Our Earth for grade V elementary schools. The research method used is research and development (RnD) by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The data sources for this research are the results of validation from two validators, the results of student response questionnaires, the results of practicality questionnaires. The data collection techniques for this research are interviews and questionnaires. The research results show that during the development process of PowerPoint-based interactive learning media, it was carried out in five stages, namely the analysis, design, development, implementation and evaluation stages. The validity of PowerPoint-based interactive learning media products in science and science learning, whatever material there is on our earth, class V of SD Negeri 17 Pontianak City obtained an average of 94.9% in the "very feasible" category. The results of student responses obtained "very good" criteria with an average score of 90.2% in limited trials and 93% in wide-scale trials. The practicality results in the limited trial obtained the criteria "very practical" with an average score of 91.2%. In wide-scale trials, an average of 90.5% was obtained in the "very practical" category. Meanwhile, the teacher's practical results obtained an average score of 100% in the "very practical" category.